PELAYANAN PENGUJIAN PIPA HDPE UNTUK APLIKASI SALURAN AIR BAWAH TANAH - Tubagus Noor Rohmannudin; Sulistijono .; Budi Agung Kurniawan; Lukman Noerochiem; Willy Deviet Kusuma (-, 2023)
The material chemistry laboratory is a laboratory which having facilities to provide teaching, research, and community dedication. One example of community dedication that the material chemistry laboratory does is by giving testing and research service to a certain institution. In this service, testing regarding HDPE pipe quality that will be applied for underground waterways is done. HDPE is a plastic material with flexible and impact-resistant properties. this material is commonly used in the industrial world, especially as a main material for pipes. In the pipe production process, good qualification of pipe is necessary. To determine the quality of the HDPE pipe, a hydrostatic pressure test, tensile test, and expansion test is done. after the testing, the result obtained for the hydrostatic pressure test is in good condition, and for the tensile test and expansion test the result is in accordance with the quality requirement of SNI 4829.2 : 2015.